Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan Pada PT. Cipta Griya Dewata Di Denpasar - Arini, Si Luh Manik; Hartati, Putu Sri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The role of human resources is very important for companies in managing and utilizing employees so that they can function productively to achieve company goals. The formulation of the problem and the purpose of this study was to determine the effect of work stress and work environment on employee morale. The population in this study were all employees of PT. Cipta Griya Dewata in Denpasar, totaling 35 employees. The analysis technique used is multiple linear regression analysis. The results showed that (1) work stress had a negative and significant effect on morale, (2) the work environment had a positive and significant effect on morale, (3) work stress and work environment simultaneously had a significant effect on work morale. Based on the results of the research, the leadership of PT. Cipta Griya Dewata in Denpasar is expected to be able to provide a workload in accordance with the SOP (standard company procedure), regularly hold meetings to sit together to coordinate, the leadership of PT. Cipta Griya Dewata in Denpasar is also expected to give warnings and sanctions to employees who often violate regulations.